PENERAPAN MODEL KOOPERATIF TIPE TSTS TERHADAP PENINGKATAN HASIL BELAJAR IPA SISWA SD - Nurhayati Selvi; Wahyullah Alannasir (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2018)
This study aims to determine the increase in science learning outcomes through the TSTS type cooperative model for elementary students. Descriptive qualitative approach with type of classroom action research. Research focus of teacher, student and learning outcomes fator. The research subjects were 24 students of SDN No. 162 Poleonro 2016/2017 school year. Data collection techniques for observation, tests and documentation. Quantitative and qualitative analysis techniques with a success indicator of 70% of students scored above 78. The results showed the application of the TSTS type cooperative model in science learning in class V SD was carried out according to the plan in each cycle. Teachers and students are able to make improvements from the results of reflection on the actions of the first cycle of action in the next cycle. So that the application of the cooperative model Type TSTS can improve the learning outcomes of grade V elementary school students. Where in each cycle has increased learning outcomes, namely in the first cycle (first) students are still confused with their role in the group and in the second cycle (second) all students act according to their role in the group.